2009
DOI: 10.1371/journal.pone.0007084
|View full text |Cite
|
Sign up to set email alerts
|

SBDS Expression and Localization at the Mitotic Spindle in Human Myeloid Progenitors

Abstract: BackgroundShwachman-Diamond Syndrome (SDS) is a hereditary disease caused by mutations in the SBDS gene. SDS is clinically characterized by pancreatic insufficiency, skeletal abnormalities and bone marrow dysfunction. The hematologic abnormalities include neutropenia, neutrophil chemotaxis defects, and an increased risk of developing Acute Myeloid Leukemia (AML). Although several studies have suggested that SBDS as a protein plays a role in ribosome processing/maturation, its impact on human neutrophil develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 31 publications
3
30
0
1
Order By: Relevance
“…To further explore the mechanism underlying the hypoplastic pancreas phenotype of Sbds ATG MO-injected embryos, we analyzed phospho-histone H3 (pHH3) labeling of ptf1a-expressing pancreatic progenitor cells at 48 hpf. Similar to previous reports suggesting that Sbds might influence cellular proliferation (Zhang et al, 2006;Orelio et al, 2009), we observed a decrease in the number of pHH3-positive mitotic cells within the ptf1a:eGFP-defined pancreatic progenitor population at 48 hpf ( Fig. 2E), with several sbds morphant embryos showing a complete absence of pHH3 labeling within the ptf1a:eGFP expression domain.…”
Section: Loss Of Sbds Results In Defective Proliferation Of Pancreatisupporting
confidence: 91%
“…To further explore the mechanism underlying the hypoplastic pancreas phenotype of Sbds ATG MO-injected embryos, we analyzed phospho-histone H3 (pHH3) labeling of ptf1a-expressing pancreatic progenitor cells at 48 hpf. Similar to previous reports suggesting that Sbds might influence cellular proliferation (Zhang et al, 2006;Orelio et al, 2009), we observed a decrease in the number of pHH3-positive mitotic cells within the ptf1a:eGFP-defined pancreatic progenitor population at 48 hpf ( Fig. 2E), with several sbds morphant embryos showing a complete absence of pHH3 labeling within the ptf1a:eGFP expression domain.…”
Section: Loss Of Sbds Results In Defective Proliferation Of Pancreatisupporting
confidence: 91%
“…44 Although these findings provide evidence for a role of SBDS in ribosome biogenesis, SBDS is a multifunctional protein, and nonribosomal activities may play a dominant role in the clinical phenotype. In particular, SBDS has been shown to have a role in stabilizing the mitotic spindle, 46,47 which might indicate a role for SBDS in proliferation and/or chromosome segregation, thereby contributing to chromosomal instability and some component of bone marrow failure.…”
Section: Q؊ Syndromementioning
confidence: 99%
“…72 Observations of in vitro assays for abnormalities of marrow stroma from SDS patients have varied. 73,74 A variety of cellular phenotypes has been observed in SDS, including mitotic spindle destabilization, 75,76 Fas ligand-induced apoptosis, 77 heightened cellular stress responses 78 and Rac2-mediated monocyte migration, 79 decreased mitochondrial membrane potential and oxygen consumption, and increased the production of reactive oxygen species. 80,81 SBDS promotes the release of EIF6 from the pre-60S ribosome, which is required for the formation of a mature 80S functional ribosome [82][83][84] (Figure 2).…”
Section: Shwachman-diamond Syndrome: Molecular Pathophysiologymentioning
confidence: 99%